PERSEPSI MAHASISWA AKUNTANSI TERHADAP AKUNTABILITAS DAN TRANSPARANSI KEUANGAN PARTAI POLITIK - Kholmi, Masiyah (Journal of Innovation in Business and Economics, 2010)
The objectives of this research to know in the perceptions of the accounting students and post graduate on accountability and transparency toward the financial in political party. The uses descriptions study method approach. The  result of the research are: 1.  The accounting students and post graduate have to this similar view on accountability and transparency toward the financial in political party; 2. Financial accountability and transparency in political party is low.